Answer:
(a) x is a variable, t is a constant
(b)t=-2/5
Explanation:
Given f(x) defined below:
![f(x)=(x+t)/(3tx+1)](https://img.qammunity.org/2023/formulas/mathematics/college/n0xszkgzks756ew4tjyv7x0sa5hcfiyw7u.png)
Part A
The value of x can take on any value, which means, it varies.
• Thus, x is a variable.
Since the function, f(x) is a function of x, t is a constant.
Part B
If f(3)=-1
![f(3)=-1\implies f(x)=-1,x=3](https://img.qammunity.org/2023/formulas/mathematics/college/urw0cn3vv636e3whem8oyo910y9jdgcj3l.png)
Substitute into f(x) above.
![f(x)=(x+t)/(3tx+1)\implies-1=(3+t)/(3t(3)+1)](https://img.qammunity.org/2023/formulas/mathematics/college/d1t6ngun38cvsy6nk114a4y6937sovo54e.png)
Cross multiply
![-1(9t+1)=3+t](https://img.qammunity.org/2023/formulas/mathematics/college/u2g389cs1y5s8ly7zqez82dr59doyc8u6q.png)
Distribute the bracket on the left-side.
![\begin{gathered} -9t-1=3+t \\ \text{Collect like terms.} \\ -9t-t=3+1 \\ -10t=4 \\ t=(4)/(-10) \\ t=-(2)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ozn13jz467j9ge06o37bhr6h8u408r7eu7.png)
The value of t when f(3)=-1 is -2/5.